2023
DOI: 10.3390/ijerph20064976
|View full text |Cite
|
Sign up to set email alerts
|

Transformative Social and Emotional Learning (T-SEL): The Experiences of Teenagers Participating in Volunteer Club Activities in the Community

Abstract: Beginning with social inequities in terms of access to quality, inclusive education for children from disadvantaged backgrounds, especially rural teenagers who leave school early, the Holtis Association, with the support of the UNICEF Representative in Romania, developed a number of interventions intended to facilitate the transition from lower to higher secondary education of students from vulnerable and disadvantaged groups. One of the interventions was the establishment of teenagers’ clubs for volunteer act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…The summarized comparison of the overall average learning activity results in the pre-cycle, cycle I, and cycle II is presented in detail in Figure 6. Through observation and reflection, it was found that the implementation of Social Emotional Learning has led to positive changes in the social and emotional aspects of students (Cojocaru, S., 2023). Students have shown improvement in their communication skills, harmonious group work, and effective emotional management.…”
Section: Reflectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The summarized comparison of the overall average learning activity results in the pre-cycle, cycle I, and cycle II is presented in detail in Figure 6. Through observation and reflection, it was found that the implementation of Social Emotional Learning has led to positive changes in the social and emotional aspects of students (Cojocaru, S., 2023). Students have shown improvement in their communication skills, harmonious group work, and effective emotional management.…”
Section: Reflectionmentioning
confidence: 99%
“…The implementation of Social Emotional Learning in ecosystem material aims to help students develop a better understanding of ecosystems and acquire the social and emotional skills necessary to collaborate in that context (Mahoney, J., et al, 2021). By increasing their self-awareness of the importance of ecosystem preservation and building empathy towards living beings within it, students are expected to become more caring and responsible individuals towards the environment (Cojocaru, S., 2023). Additionally, Social Emotional Learning also emphasizes the development of social skills such as communication, teamwork, and conflict management (Dermody, C. M., et al, 2022).…”
Section: Introductionmentioning
confidence: 99%